Remote assessments of human pressure on biodiversity may miss important human threats. Issue 1 (4th December 2022) - Mammides, Christos; Martini, Francesco; Kounnamas, Constantinos
Abstract: Monitoring human pressure on biodiversity within protected areas (PAs) remains a challenging task due to the vast number of PAs worldwide (>250, 000) and the fact that we lack basic information for most of them. Consequently, researchers are increasingly relying on remote sensing techniques to overcome this challenge. However, remote assessments of human pressure on biodiversity may miss crucial threats, such as hunting and invasive species, which are often best documented through in situ field surveys. Here, we use a unique European Union dataset documenting human threats within 8210 PAs through field surveys to assess the relationship between those threats and three commonly used indices of human pressure that are largely derived using remote‐sensing methods—the Human Footprint and Human Modification indices and the LandScan Global Population Database. We find that the indices are not always related to the threats recorded within PAs through field surveys. The indices seem to best capture threats associated with urbanization, agriculture, and pollution but not necessarily others. Although remote assessments of human pressure on biodiversity are crucial for conservation, researchers and practitioners must be aware of their limitations and must complement such assessments with information collected in the field whenever possible. Abstract : Recent advances in remote sensing technology and computing processing power have made remote sensing data increasingly useful for assessing human threats within protected areas across large scales. However, such assessments are restricted to human threats and activities that can be captured remotely. Consequently, other key threats, such as hunting and invasive species, may go undetected, potentially biasing our conservation efforts. 摘要: 全球有超过25万个保护区，其中大多数缺失基本信息，使得在保护区内开展人类活动对生物多样性胁迫的监测成为一项具有挑战性的任务。因此，研究人员越来越依赖遥感技术来克服这一挑战。然而，遥感评估可能缺失某些关键胁迫，如捕猎和外来物种入侵，这些信息通常能通过实地调查获得最好的记录。本研究采用欧盟Natura 2000自然保护区网络中记录的来自8210个保护区实地调查的人类胁迫数据，来评估这些胁迫与三个常用人类压力指数之间的关系。这三个人类压力指数通常通过遥感方法获取，分别为:人类足迹指数、人类改造指数和LandScan全球人口分布数据。研究发现，这些指数并不总是与保护区内实地调查的胁迫相关。这些指数似乎能很好地体现与城市化、农业和污染相关的胁迫，但不一定能体现其他胁迫。尽管遥感技术在评估人类活动对生物多样性的影响方面至关重要，但研究人员和保护工作者须认识到遥感技术的局限性，并尽可能补充实地调查的信息来进行综合评估。